Bentuk Penyajian Tari Babuai Duduak di Kampung Laban Salido Kecamatan IV Jurai Kabupaten Pesisir Selatan Sumatera Barat - Silvi Oktari Aska; Adriana Gusti; Eva Riyanti (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This journal examines the presentation form of Babuai Duduak dance in Laban Salido Village, IV Jurai District, Pesisir Selatan Regency, West Sumatra. This research uses a qualitative method that is descriptive analysis. The theory used is the theory of form proposed by Sal Murgiyanto. The results of the study show that Babuai Duduak dance has three basic elements, namely the performers, the audience and the content conveyed. The presentation form of Babuai Duduak dance has dance elements, namely dancers, movements, music, makeup, costumes, property, floor patterns and performance venues.